CONVERSION OF CELLULOSE TO 5-HYDROXYMETHYLFURFURAL AS SUSTAINABLE ENERGY: A BIBLIOMETRIC ANALYSIS BY VOSVIEWER - Faradis, Royyan; Suryanto, Ardiansyah Bagus; Murwani, Irmina Kris (Journal of Environmental Science and Sustainable Development, 2023)
The developments of the global economy and society impact resources and the environment. This condition requires an alternative to find new, safe, and sustainable energy types. The conversion of cellulose to 5-hydroxymethylfurfural (5-HMF) has become a significant area of research interest. It has triggered the development of research directions related to biomass and energy because it can be an intermediary source for making polymers, solvents, pharmaceuticals, and biofuels. The primary objective of this study is to give a bibliometric analysis of 1753 reports on the development of research on cellulose conversion to 5-HMF from 1965 to 2021. The data were gathered from the Scopus database using the keywords “conversion of cellulose” and “5-HMF”, and they were then subject to content and bibliometric analysis. VOSviewer is a software used for data analysis that can visualize the linkages and map the outcomes of particular study objects. The results show increased annual publications in the last five years with cross-disciplinary collaborations in scientific fields. In terms of publications, the United States tops other nations (550 documents), whereas Indonesia is rated 34th (15 documents). Based on VOSviewer analysis, the overlay visualization of research trends by year shows that the keyword of the process of converting cellulose to 5-HMF is a relatively recent study topic compared to other cellulose topics. By identifying specific suggestions and strategies for the development and utilization of biomass energy based on the analysis of the relationship and interaction between the utilization of biomass energy and the environment, this work is beneficial for researchers to choose future research topics.